Peningkatan Hasil Belajar Matematika Materi Kesebangunan dan Kekongruenan melalui Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) dengan Pendekatan Scientific pada Peserta Didik - Yulianis, Yulianis (Mataram University, 2021)
This research aims to find out the improvement of learning outcomes through the application of the Think Talk Write (TTW) Type Cooperative Learning Model with the Scientific Approach of class IX.3 State Junior High School 9 Dumai. This type of research is a classroom action research or classroom action research (CAR) that has 4 stages (planning stage, implementation stage, observation stage and reflection stage). The research conducted with the Observer was a fellow researcher. Observations are made on teacher activities, student activities and learning outcomes carried out in two implementation cycles consisting of cycle I and Cycle II. The results of research in cycle I obtained the activities of Teachers and learners during the learning process 74% and 75% which are in the category is quite good, with the learning outcomes of learners classically for cycle I has not reached the desired success indicator which is 75%. Furthermore, in cycle II, teacher and student activities during the learning process of 90% which are in the category are very good, with the learning results of learners classically get the completion of learning 96% so that the completion of learning learners classically for cycle II has been achieved, namely â‰¥75%. So it can be concluded that the application of TTW cooperative learning model with a scientific approach to mathematics lessons with revival and support materials can improve student learning outcomes in class IX.3 State Junior High School 9 Dumai